Operation and application of correctional work aimed to moving function development and their influence on higher nervous activity development - Ermolova Z. A. (Preschool education: experience, questions and future development, 2016)
в статье представлены результаты анализа влияния своевременного развития мелкой моторики на развитие речи детей.
Keywords: упражнения; мелкая моторика; развитие мелкой моторики